Uji Antibakteri Ekstrak Etanol Daun Tumbuhan Liar Kipahit (Tithonia diversifolia) Terhadap Pertumbuhan Bakteri Salmonella typhi Secara In-Vitro - Ika Peronika PERONIKA; Dhiah Novalina; Farida Noor Irfani (LPPM Universitas Abdurrab, 2025)
Tithonia diversifolia, commonly known as Kipahit, is a wild plant with promising potential as a natural antibacterial agent due to its effectiveness in suppressing bacterial multiplication. This study aimed to evaluate the antibacterial inhibitory power of ethanol extracts from Kipahit leaves against Salmonella typhi and to determine the most effective concentration for inhibiting its growth. To isolate the active constituents from Kipahit leaves, a maceration technique was employed, with 96% ethanol acting as the organic solvent. The disc diffusion method (Kirby-Bauer) was employed to determine antibacterial potency. The presence of a clear halo around the disc demonstrated the compound's capacity to hinder bacterial growth. SPSS 27 was used for data analysis, which involved normality testing (p > 0.05), Kruskal-Wallis testing, and Mann-Whitney U testing to determine significant variations between the treatment group. The highest antibacterial activity was observed at an extract concentration of 70% (categorized as sensitive), while the 10% extract still demonstrated an inhibitory effect classified as intermediate. Statistically, both 40% and 70% concentrations showed significant differences when compared to the negative control. A noticeable difference also emerged when these concentrations were pitted against the 1% chloramphenicol positive control. A clear positive correlation also existed between the concentration of the extract and the diameter of the inhibition zone that developed. Keywords: Antibacterial, Tithonia diversifolia, Salmonella typhi, In-Vitro